2002
DOI: 10.1177/039139880202500507
|View full text |Cite
|
Sign up to set email alerts
|

Dialysis in Adults in Year 2000 in the Republic of Macedonia

Abstract: 1,019 adult patients with terminal renal failure were treated with dialysis (D) in the first part of the year 2000 in the Republic of Macedonia. 1,010 patients (99%) were treated with chronic intermittent (maintenance) hemodialysis (HD) while nine patients (1%) were on continuous ambulatory peritoneal dialysis (CAPD). For the children, a special peritoneal dialysis program was developed; 509 patients per million of the population (PMP) were on dialysis. The Republic of Macedonia is, therefore, among those cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…We have previously shown that the number of diabetics on dialysis in RM enlarges slowly but progresively [65][66][67][68]. In current analysis, beside the fact that mean total prevalence of DM was just slightly increased as compared to our previous studies [66], we show that there is an important difference in prevalence of diabetics on dialysis between different dialysis centres.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…We have previously shown that the number of diabetics on dialysis in RM enlarges slowly but progresively [65][66][67][68]. In current analysis, beside the fact that mean total prevalence of DM was just slightly increased as compared to our previous studies [66], we show that there is an important difference in prevalence of diabetics on dialysis between different dialysis centres.…”
Section: Discussionsupporting
confidence: 49%
“…The number of patients with diabetic nephropathy progressing to the point of need for renal replacement therapy and renal transplantation is also increasing [65][66][67]. Given the fact of lack of data and valuable epidemiological studies in these patients, we performed a nation wide study with the aim of defining prevalence of these patients in RM, determining the standards of care in diabetics in term of methodological approach, dialysis and drug treatment and analysis of these patients on dialysis.…”
Section: Diabetics On Dialysis In the Republic Of Macedoniamentioning
confidence: 99%
“…This can be attributed to the poor connection between primary care and referral to specialized dialysis units. These numbers remain low compared to leading and neighboring countries (4-6); however, in 2001, acceptance rates for RRT exceeded 100 per million population for the first time.…”
Section: Numbers Of Patients Treatedmentioning
confidence: 93%